The Effect Of Green Accounting and Intellectual Capital On Firm Value - Alfonsa Dian Sumarna; Rismawanti (University of Merdeka Malang, 2025)
This study examines the influence of green accounting and intellectual capital on firm value, focusing on mining companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Using purposive sampling, 112 companies meeting specific criteria were selected as the sample. Green accounting was measured by ISO 14001 certification, intellectual capital was assessed using the Value-Added Intellectual Coefficient (VAIC), and firm value was evaluated through the Price-to-Book Value (PBV) ratio. The findings reveal that neither green accounting nor intellectual capital has a significant impact on firm value in the observed context. The results suggest that, within Indonesia's mining sector, environmental certification and intellectual capital may not yet be key drivers of firm valuation. This could indicate a need for stronger regulatory frameworks or market incentives to enhance the financial relevance of sustainability and intangible assets. Future research could investigate additional variables, such as corporate governance or market perceptions, to gain a deeper understanding of these dynamics.